Universal health coverage in Lebanon: agenda setting using Kingdon's model and a proposed legal framework for revenue allocation - Mouawad, Joseph; Lteif, Maria Rita; Mina, Wadih; Karam, Rita (Frontiers in Health Services, 2025)
BackgroundHealth systems globally aim for Universal Health Coverage (UHC), however progress toward UHC remains challenging in many countries. Despite previous unsuccessful parliamentary attempts to secure national commitment to a UHC plan in Lebanon, a renewed and revised effort is currently being made by a dedicated parliamentary committee. This study has two main objectives: to examine the emergence of the UHC bill as a priority on the Lebanese policy agenda using John Kingdon's Framework; and (2) to conduct a policy analysis using Bardach and Patashnik's eight-step framework to identify the most suitable funding option for the proposed UHC program.MethodsTwo policy analysis frameworks were applied: John Kingdon's model, commonly used to study agenda setting, and Bardach and Patashnik's eight-step framework, designed to evaluate policy options and recommend evidence-based solutions. A qualitative document analysis was conducted using the READ approach drawing on secondary literature sources. Data triangulation was also used to ensure consensus and accuracy.ResultsThe document analysis identified the emergence of a window of opportunity for the UHC bill as the three streams aligned: mounting public pressure, the formation of a parliamentary committee, and evident political receptiveness through the involvement of multiple parties. Bardach & Patashnik's policy analysis framework identified earmarked excise taxes as the most suitable policy alternative for financing UHC in Lebanon.ConclusionThis study explains the emergence of an updated UHC bill on the Lebanese policy agenda while conducting a policy analysis of the earmarked excise taxed to fund UHC. To overcome anticipated challenges a legislative framework must be established to ensure transparency in funding and government accountability.